Doctoral Students’ Experiences in Writing For Publication: The Case of One Doctoral Program in Jambi University - Mayang Sastra Sumardi; Aryawira Pratama; Rahmadania Putri (Edumaspul: Jurnal Pendidikan, 2022)
Writing scientific papers for publication is a major and common requirement for students pursuing postgraduate studies. The purpose of this article is to discuss the experiences of doctoral students in writing scientific papers to be published in reputable journals and what are the challenges of doctoral students (discursive and non-discursive) in writing scientific papers for publication in reputable journals. The findings indicated the undrgraduated students' positive attitude on writing for publication in international journal because many participants are the lecturers and also the teachers. They thought it will be important to publish an article especially in international journal to support their career because they are demanded to publish article regularly. But most of them are not from English department so they found some difficulties related to the language. They find difficulties in translating their L1 to English. They have lack of knowledge about English such as grammar, lack of suitable vocabulary,etc. The doctoral students also found challenges in writing their article. There are two main challenges that the researcher found in this research. They are discursive challenges and no-discursive challeges